Models for forecast-analytical assessment of the economic and managerial transformation of a construction enterprise’s operating system - Krychevska , Yu. (Ways to Improve Construction Efficiency, 2023)
The article explores innovative applied approaches to the structural-functional regulation of the operational system of construction development companies. It highlights the importance of implementing the latest technologies and management solutions to optimize operational processes in the construction sector. The advantages of digital solutions, automation, Building Information Modeling (BIM), and control systems to improve the efficiency of development companies are analyzed separately. The article also examines the impact of innovations on the regulation and standardization of processes, contributing to increased productivity and quality of construction projects. This foundation provides a clear structure of functions and operations performed by the company, establishes task execution standards and rules, and aids in adapting the business to new market challenges. Such innovations reduce costs, improve productivity, enhance project execution quality, and strengthen the company’s competitiveness in the construction market. The article also addresses forecast-analytical assessment models for evaluating the effectiveness of economic and managerial transformation within the operational systems of construction development enterprises. Special attention is given to tools such as PESTEL analysis, SWOT analysis, Balanced Scorecard, financial ratio analysis, scenario planning, and Economic Value Added (EVA) modeling. Key performance indicators are identified that enable forecasting and evaluating the impact of changes on the enterprise's operating system. The presented models, including elasticity analysis and cost optimization models, comprehensively assess the impact of management and economic factors on operational performance. These models assist construction developers in adapting management strategies to changing market conditions, reducing risks, enhancing operational efficiency, and increasing competitiveness. The article also reveals the advantages of applying forecasting models during transformation and offers practical recommendations for their use in the strategic development of construction enterprises.